Prevalence of Intestinal Parasitic Infections and Associated Risk Factors Among Schoolchildren in Ibb Governorate, Southwest Yemen: A Cross-Sectional Study - Al-Fakih AA; Al-wrafi EA; Al-motawkil AAHAAJ; Shabalah AZA; Aqeel AF; Mahdi MA; Al-hubaishi HA; Marsh YM; Joyer BH; Al-shoga'a GH (Dove Medical Press, 2022)
Abdulkawi Ali Al-Fakih,1,2 Essam Ali Al-wrafi,3 Amat Al-haleem Abdu Al-jabar Al-motawkil,3 Al-zahra Ali Shabalah,3 Asma Faisal Aqeel,3 Mohammed Abdallah Mahdi,3 Haneen Abdualkareem Al-hubaishi,3 Yahya Mansour Marsh,3 Bothina Hassan Joyer,3 Ghada Hossain Al-shoga'a3 1Department of Medical Microbiology, Faculty of Science, Ibb University, Ibb, Yemen; 2Faculty of Allied Medical Sciences, Aljazeera University, Ibb, Yemen; 3Department of Medical Laboratories, Faculty of Allied Medical Sciences, Aljazeera University, Ibb, YemenCorrespondence: Abdulkawi Ali Al-Fakih, Department of Medical Microbiology, Faculty of Science, Ibb University, Ibb, Yemen, Tel +967 771950569, Fax +967 04413766, Email fakeeh830@gmail.comIntroduction: Intestinal parasitic infections (IPIs) among schoolchildren are important public health problem, especially in developing countries, and monitoring of such infections and associated risk factors are necessary for intervention strategies. In line with this view, the aim of this study was to determine the prevalence of IPIs and associated risk factors among schoolchildren in Ibb governorate, southwest Yemen.Methods: A cross-sectional study was carried out during February to April 2020 on 600 schoolchildren selected from 6 districts of Ibb governorate. Fecal specimens were examined using saline and iodine wet mount and formal-ether concentration techniques. Socio-demographic data were collected using pre-designed, structured questionnaires. The results were analyzed using SPSS for Windows version 25 (SPSS Inc., Chicago, IL, USA).Results: Out of 600 participants, the overall prevalence of IPIs was 66.3% (398/600). The prevalence rate of protozoan infections (56.3%, 338/600) was largely higher than helminthic infections (10%, 60/600). The most common intestinal parasite was E. histolytica/dispar (28.5%, 171/600). S. mansoni infection showed higher infection rate in males (5.3%) than in females (0.4%), with statistically significant difference (P = 0.001). Univariate analysis showed that the age was only significantly associated with protozoan infections, with statistically significant differences (P = 0.002). Regarding to clinical symptoms, the presence of IPIs was significantly associated with diarrhea, dysentery, and abdominal pain.Conclusion: The present study revealed that there was a relatively high prevalence of IPIs, especially protozoan parasites, in schoolchildren of the study area, with E. histolytica/dispar being the most prevalent parasite. The results showed that age was only significantly associated with IPIs. According to the results of this study, IPIs are still among the main public health problems in the study area. Thus, effective prevention and control strategies are important to reduce the incidence of IPIs in this area of the country.Keywords: prevalence, intestinal parasitic infections, schoolchildren, Yemen